THE MODERATING ROLE OF AGENCY COST ON THE RELATIONSHIP BETWEEN CAPITAL STRUCTURE AND FIRM PERFORMANCE: EMPIRICAL EVIDENCE FROM INDONESIA STATE-OWNED ENTERPRISES - Purusotomo, Bayu Antarikso; Hadinugroho, Bambang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Purpose – The Indonesian government's plan to focus more on infrastructure is an opportunity for State-Owned Enterprises (SOEs) in Indonesia specially in construction sector. Joko Widodo, as the President of the Republic of Indonesia stated, despite various inputs, the government decided to focus on infrastructure development in 2015. With the large-scale construction project, SOEs in construction sector will attempt to achieve an optimal capital structure in order to continue the company’s operations. The purpose of this paper is to explore the moderating role of agency cost on the relationship between capital structure and firm performance. Design/methodology/approach – Using 63 data observations of 7 Indonesia SOEs in construction sector for the period from 2010 to 2019. Multiple Regression Analysis and Moderated Regression Analysis is used to investigates the moderating role of agency cost on the relationship between capital structure and firm performance. Finding – The results indicate that the capital structure has positive effect on ROE. Furthermore, agency cost appears to moderate the relationship between capital structure and firm performance. The means of capital structure and performance before and during Joko Widodo era were analyzed using t-test. Significant difference was found between the groups before and during Joko Widodo era. This result shows that the capital structure and performance of SOEs changed following the infrastructure development policy. Practical implications – This research is to provide further enrichment related to the problem of inconsistency in the relationship between capital structure and firm performance in agency cost hypotheses. In addition, this study provides an overview of the optimal capital structure, especially for SOEs in the construction sector in Indonesia. Originality/value – Despite the extensive research done on the area of capital structure since 1958, understanding in the area is still inconclusive specially in SOEs. The policy of infrastructure development in 2015 insist SOEs to achieve an optimal capital structure in order to continue the company’s operations. Thus, how SOEs manage their capital structure? Keyword Capital Structure, Agency Cost, Firm Performance, SOEs, Construction Sector Paper type Research paper